PERFORMANCE OF DURABILITY CHARACTERISTICS ON HIGH STRENGTH CONCRETE USING NANO CLAY, RED MUD AND SILICA FUME ADMIXTURES - Khazalah, Dr.Mahmoud Al; Rajesh, A.Maria; Joe, M.Adams (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
The paper deals with the performance of durability characteristics using Nano clay, red mud and silica fume to produce a high strength concrete. This study is mainly concentrated on the durability characteristics of HSC with some percentage replacement of cement by red mud, nano clay and silica fume. The cement was replaced with 75% to 60% at 2.5% interval by mineral admixture such as red mud, nano clay and silica fume. Water cement ratio is kept constant for all mixtures. The main aim of paper is to be found out the acid and chloride resisting capacity of the specimens. The result shows that the combination of third sample produced 20% more resisting capacity of acid and chloride immersion compared with other samples from the experimental.